HUBUNGAN ANTARA IMT DENGAN USIA MENARCHE PADA SISWI SD DAN SMP DI KOTA MANADO - Munda, Sarah Stevany (Universitas Sam Ratulangi, 2013)
Abstract: Menarche is the first menstruation experienced by woman. The improving standards of life will impact on the age of menarche (early menarche). There are many factors that affect the age of menarche, one of them is nutritional status. This research was aimed to analyze correlation between the nutritional status and age of menarche in female student of elementary school and junior high school at Manado city. This research used a cross sectional study. The subject was 196 female student. The data was analyzed using chi-square test. Research result showed that average age of menarche in elementary school is 10.63 ± 0.72 and in junior high school is 11.34 ± 1.35. Based on test results X2 (Pearson Chi Square) value obtained X2 = 68.742, p = 0.000. These results indicate that there is a highly significant association between IMT and age of menarche (p <0.01).Keywords: Female student, Menarche age, Nutrinional statusAbstrak: Menarche adalah menstruasi pertama yang dialami oleh seorang wanita. Membaiknya standar kehidupan berdampak pada penurunan usia menarche (menarche dini). Ada banyak faktor yang mempengaruhi usia menarche, salah satunya adalah status gizi. Penelitian ini bertujuan untuk menganalisis hubungan antara status gizi dan usia menarche pada siswi di SD dan SMP di Kota Manado. Penelitian ini menggunakan desain penelitian cross-sectional dengan sampel sebanyak 196 siswi. Data akan dianalisis dengan uji chi square. Hasil penelitian menunjukkan rata-rata usia menarche di SD adalah 10,63 ± 0,72 dan SMP adalah 11,34 ± 1,35. Berdasarkan hasil uji X2 (pearson Chi Square) diperoleh nilai X2 = 68,742 dengan p = 0,000. Hasil ini menyatakan terdapat hubungan yang sangat bermakna antara IMT dan usia menarche (p < 0,01).Kata kunci: Siswi, Status gizi, Usia menarche